2019
DOI: 10.1507/endocrj.ej18-0505
|View full text |Cite
|
Sign up to set email alerts
|

High sex hormone-binding globulin concentration is a risk factor for high fibrosis-4 index in middle-aged Japanese men

Abstract: Low endogenous testosterone and sex hormone-binding globulin (SHBG) concentrations have been reported to be associated with metabolic syndrome (MetS) and non-alcoholic fatty liver disease (NAFLD). However, little is known about the relationships between testosterone or SHBG and liver fibrosis in NAFLD. Thus, we aimed to clarify the relationships between serum testosterone or SHBG concentration and fibrosis-4 (FIB-4) index, a marker of liver fibrosis. Serum testosterone was assayed in various forms (total testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
3
10
1
Order By: Relevance
“…This implies that FIB-4 index may represent a predictor for the risk of developing DM in non-diabetic Japanese people. This finding is not consistent with those of previously published studies, in which NAFLD was shown to increase insulin resistance, with a compensatory increase in insulin secretion 21,22 , which is eventually followed by the development of glucose intolerance or DM when this compensatory mechanism fails [5][6][7] , while relationships of FIB-4 index with HOMA-β but not with HOMA-R were recently reported in a population-based cross-sectional study of Japanese 23 . Although we have no precise explanation for this inconsistency, differences in study samples may be responsible.…”
Section: Discussioncontrasting
confidence: 99%
“…This implies that FIB-4 index may represent a predictor for the risk of developing DM in non-diabetic Japanese people. This finding is not consistent with those of previously published studies, in which NAFLD was shown to increase insulin resistance, with a compensatory increase in insulin secretion 21,22 , which is eventually followed by the development of glucose intolerance or DM when this compensatory mechanism fails [5][6][7] , while relationships of FIB-4 index with HOMA-β but not with HOMA-R were recently reported in a population-based cross-sectional study of Japanese 23 . Although we have no precise explanation for this inconsistency, differences in study samples may be responsible.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, this group had also higher prevalence of detectable plasmatic HCVRNA. Importantly, liver fibrosis positively correlated with SHBG and TT levels as previously described [15][16][17][18][19][20][21]. As summarized in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In the general population T is reduced in up to 90% of men with cirrhosis [12] and in male patients with HCV-related chronic liver diseases [14]. In addition, the relationship between sex hormones and SHBG levels and Non Alcoholic Steato Hepatitis (NASH), Non Alcoholic Fatty Liver Disease (NAFLD) and liver fibrosis has been reported in some studies [15][16][17][18][19][20][21], although with non-conclusive data.…”
Section: Introductionmentioning
confidence: 99%
“… 88 Recent studies have demonstrated that testosterone is also closely associated with metabolic syndrome, type 2 diabetes, and NAFLD. 89 - 94 Production of testosterone gradually decreases with aging, and the prevalence of these diseases increases at an older age.…”
Section: Gender Differencementioning
confidence: 99%